Maternity Benefit - Great Britain. National Insurance Act, 1946 ([London] : H. M. Stationery Office)
1948-03 1948 1940s 8 pages If you or your husband were insured under the old scheme of National Health Insurance you should read paragraphs 15 and 16 of this leaflet. If your husband is over pensionable age or if you are a widow claiming on your late husband's insurance, special conditions apply ; these will be explained to you at any local National Insurance Office. 6. How do I obtain the Grant? You should send the completed claim form to your local National Insurance Office. You will see that the claim form is divided into four parts. Part I you must complete and sign in all cases. If you wish to have the grant paid to you before your confinement, Part III must be completed by your doctor or midwife not more than seven weeks before the week when your confinement is expected. If you do not want payment in advance, you should get Part IV of the form completed as soon after your confinement as possible. If the claim form is not received at the local office within three months after the confinement, payment cannot ordinarily be made. ATTENDANCE ALLOWANCE 7. What are the Contribution Conditions for Attendance Allowance? The same as for Maternity Grant (see paragraph 5) provided that you or your husband satisfy those conditions at the date of your confinement. 8. How do I claim the Attendance Allowance? If you have claimed Maternity Grant in advance (see paragraph 6) and have not claimed Maternity Allowance, a claim form for Attendance Allowance will accompany the payment of the grant. As soon as possible after your confinement and in any case not more than ten days afterwards the form should be returned to the local National Insurance Office signed by you (or someone acting for you) and with the appropriate part filled in by the doctor or midwife who is attending you. If more than one child is bom this form will be treated also as a claim for the additional Maternity Grant. 4 21/3848